Pelaksanaan Flipped Classroom pada Pembelajaran Bahasa Indonesia di Sekolah Dasar - wiwit rahayu, chandra; Siti Rochmiyati (Morfologi : Jurnal Ilmu Pendidikan, Bahasa, Sastra dan Budaya, 2023)
This research aims to describe learning through the flipped classroom model on Indonesian language lesson content in grade VI elementary schools at SD Negeri Sendangsari. The type of research in this research is descriptive qualitative. The research subjects were 17 class VI students in the 2023/2024 academic year. Research data was obtained through questionnaires, observation, and documentation. Questionnaires were given to students to see data on students' responses to Flipped classroom learning, observations were carried out to see the implementation of Flipped classroom learning, and documentation studies were carried out to examine students' values in learning. The data analysis used in this research is triangulation. The results of the research showed that the implementation of Indonesian language learning activities in class VI of SD Negeri Sendangsari ran smoothly. Educators carry out learning activities in the planned steps. Most students get scores above the KKM or complete. Learning with the Flipped classroom model can be well received by students so that students can get grades above the KKM after learning through the Flipped classroom model. Most students are enthusiastic about participating in learning using the Flipped classroom model.